Airflow and Temperature Modelling of Sustainable Buildings at the Design Stage can Prevent Unintended Consequences of Passive Features. (2017) - Alemu, Alemu T.; Saman, Wasim; Belusko, Martin
Abstract: The integration of passive features during the design/construction of sustainable buildings requires thorough modelling at the design stage as some features may have unintended consequences resulting in occupant dissatisfaction, and resulting in the building using more energy to maintain comfort. This paper reports the outcome of an investigation into the thermal performance of a recently built 'sustainable science building' in a school located in South Australia. The building consists of a 115 m 2 atrium which is naturally ventilated by a solar chimney integrated into a high pitch roof with low level and celestial window openings at the outlet of the chimney. The experiment was undertaken in January to monitor the airflow pattern and air temperatures at different location of the atrium. A mathematical model was used to predict the performance for comparison with experimental data. At some hours, it was observed that flow reversal in the chimney led to unwanted hot air entering into the building thus increasing the building cooling load. The model was able to predict the flow reversal at those times. The use of such a model at the design stage can help develop an improved chimney design which avoids the undesired flow reversal and demonstrates the potential value of modelling of passive features before construction.